Postoperative high-dose-rate brachytherapy alone in stage T1-3N0M0 oral cancer with negative prognostic factors: A retrospective study - Tuček, Luboš; Sirák, Igor; Pohanková, Denisa; Kašaová, Linda; Grepl, Jakub; Paluska, Petr; Hodek, Miroslav; Vošmik, Milan; Mustafa, Banni Aml; Čermánková, Eva; Petera, Jiří (Brachytherapy, 2025)
PURPOSE: To evaluate treatment outcomes and toxicity in patients with stage T1-3N0M0 oral cancer treated with surgery followed by high-dose-rate brachytherapy (HDR-BT). METHODS AND MATERIALS: Retrospective study of 50 patients with stage T1-T3N0 tongue and floor-of-mouth cancer who underwent tumour excision (+ elective neck dissection) followed by postoperative HDR-BT due to the presence of negative prognostic factors (close or positive resection margins, lymphovascular and/or perineural invasion, deep invasion). The plastic tube technique (dose: 18 x 3 Gy b.i.d.) was used. Survival outcomes, toxicity, and prognostic factors were evaluated. RESULTS: At a median follow-up of 81 months (range, 4-121), actuarial 5-year local control (LC), nodal control (NC) and progression-free survival (PFS) rates were 79%, 69%, and 64%. After salvage treatment (surgery + external beam radiotherapy), LC, NC, and PFS increased to 87%, 77%, and 72.3%, respectively. Five-year overall survival and cancer-specific survival (CSS) rates were 73% and 77%. Treatmentrelated toxicity included two cases of mandibular osteoradionecrosis and five cases of small soft tissue necrosis. T stage was significantly correlated with nodal control (p=0.02) and CSS (p=0.04). Tumour grade correlated with DFS (p=0.01). CONCLUSION: Postoperative HDR-BT 18 x 3 Gy b.i.d. seems to be an effective method in patients with T1-3N0M0 oral cancer with negative prognostic factors after tumour resection.
Keywords: dospělí; Female; Adult; výsledek terapie; ženské pohlaví; lidé; staging nádorů; Mouth Neoplasms; celková dávka radioterapie; Treatment Outcome; Aged, 80 and over; míra přežití; prognóza; Brachytherapy; retrospektivní studie; nádory úst; Male; Aged; brachyterapie; Prognosis; Survival Rate; lidé středního věku; Radiotherapy Dosage; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Neoplasm Staging; Humans